Marine outfall discharges contribute to coastal microplastic pollution and the spread of antimicrobial resistance - Raeesa Bhikhoo; Krisdan Bezuidenhout; Lesego Molale-Tom; Charlotte Mienie; Carlos Bezuidenhout (PLoS ONE, 2025)
Microplastics are widespread in marine environments, with significant contributions from land-based wastewater treatment plants (WWTPs). A desktop study was conducted on regulatory framework for marine outfalls in South African coastal cities. The South African regional policy permits proper disposal of wastewater in a marine outfall provided raw wastewater is treated and will not have an adverse effect on the receiving body. The experimental study investigated the capacity of microplastics to serve as reservoirs for multidrug-resistant (MDR) bacteria originating from WWTP effluent. Experiments challenging the regulations were based on microbiology of the effluent that is discharged through an outfall. Microcosms were set up by spiking seawater with WWTP effluent and adding the collected plastic pieces. Scanning electron microscopy (SEM) was used to determine colonization on the microplastics. After 30 days of microcosm exposure, selective media and incubation conditions were used to isolate Enterobacteriaceae. Pure isolates were tested against 16 antibiotics normally used in human clinical settings. In the initial biofilms directly from microplastics from the WWTPs, several genera generally associated with wastewater treatment were isolated. Dominant species isolated and identified were Citrobacter sp., Escherichia sp., Enterobacter sp., Serratia sp., Klebsiella sp. and Pseudomonas sp.. Several isolates were resistant to the last resort of antibiotics, (doripenem and imipenem; 9% to 27%) and some of these isolates were resistant to up to ten of the antibiotics. These findings highlight that clinically relevant Enterobacteriaceae colonize microplastics and survive in biofilms on these microplastics surfaces. Bacterial infections caused by Carbapenem-resistant Enterobacteriaceae have become a global concern in the fight against bacterial infections. Our findings highlight the need for more data to challenge existing marine outfall policies and the outdated notion stating that dilution alone can solve pollution problems.